Morphological Characterization and Phylogenic Assignment of Two New Species in Genus Metopus (Ciliphora, Armophorea) Collected from North China - Qianrui Niu; Yunfeng Wang; Daode Ji (Journal of Ocean University of China, 2026)

Methane emission fluxes and associated microbial community characteristics in a temperate seagrass meadow - Wenwen Tan; Zhihai Zhong; Qianling He; Xin Yun; Lin Yang; Xin Wang; Daode Ji; Guangyu Wang; Jianmin Zhao; Xiaoli Zhang (Science of The Total Environment, 2025)

Effect of Mariculture on Planktonic Protist: A Case Study in a Marine Ranch of Northern Yellow Sea, China - Chenchen Zhao; Xiaoxin Zhang; Wenjing Zhang; Ning Xu; Xiaoli Zhang; Jianmin Zhao; Qianqian Zhang; Daode Ji (Journal of Ocean University of China, 2024)

N2O emission in temperate seagrass meadows: Fluxes, pathway and molecular mechanism - Qianling He; Huawei Qin; Lin Yang; Wenwen Tan; Daode Ji; Jianbai Zhang; Xiaoli Zhang (Marine Environmental Research, 2024)

Correction to: Salinity Acclimation Induces Reduced Energy Metabolism, Osmotic Pressure Regulation and Transcriptional Reprogramming in Hypotrichida - Xin Ji; Luping Bi; Songbao Zou; Wenlu Li; Daode Ji; Qianqian Zhang (Journal of Ocean University of China, 2024)

Salinity Acclimation Induces Reduced Energy Metabolism, Osmotic Pressure Regulation and Transcriptional Reprogramming in Hypotrichida Ciliate Gastrostyla setifera - Xin Ji; Luping Bi; Songbao Zou; Wenlu Li; Daode Ji; Qianqian Zhang (Journal of Ocean University of China, 2024)

Detection of Prokaryotes on the Astomatous Ciliated Protist Kentrophoros flavus (Ciliophora, Karyorelictea) Revealed A Consistently Associated Muribaculaceae-Like Bacterium - Luping Bi; Xiaoxin Zhang; Songbao Zou; Daode Ji; Qianqian Zhang (Frontiers in Marine Science, 2022)
The interactions between symbiotic bacterial consortia and their protist hosts in benthic environments have attracted increasing interest in recent years. In the present study, we investigated the diversity of potentially associated bacteria for an astomatous ciliate, Kentrophoros flavus , collected in the intertidal zone of Yantai, China. For the first time, the diversity of the associated bacteria in the species K. flavus was examined using 16S rRNA-based techniques (clone libraries and PacBio sequencing) and the fluorescence in situ hybridization (FISH) technique. The 16S rRNA-based sequencing revealed a higher diversity of associated bacteria in K. flavus than previously expected. In addition to a genus-typical thiotrophic symbiont, the “ Candidatus Kentron” stain YE, we provide evidence showing the consistent existence of one Muribaculaceae -like bacterium that was secondarily abundant among the bacterial operational taxonomic units (OTUs). Fluorescence in situ hybridization (FISH) with three specific probes and double-label FISH experiments with “ Candidatus Kentron” probes showed that the Muribaculaceae -like bacterium was abundant and merged with the “ Candidatus Kentron” stain YE on the cell surface of the host. A phylogenetic analysis of the bacterial 16S rRNA gene showed that the bacterium was a distinct branch in Muribaculaceae , members of which are primarily reported from gut microbiome. The name “ Muribaculaceae -like bacterium associated with Kentrophoros flavus ” (MLAKF) is proposed for the new bacterium. The higher 16S rRNA diversity in K. flavus and the discovery of MLAKF on the cell surface both suggest a potential bacterial consortium that interacts with the host K. flavus .

Protist Interactions and Seasonal Dynamics in the Coast of Yantai, Northern Yellow Sea of China as Revealed by Metabarcoding - Yingjun Fu; Pengfei Zheng; Xiaoli Zhang; Qianqian Zhang; Daode Ji (Journal of Ocean University of China, 2020)

Complementary notes on a ‘well-known’ marine heterotrichous ciliate, Folliculinopsis producta (Wright, 1859) Frauré-Fremiet, 1936 (Protozoa, ciliophora) - Daode Ji; Xiaofeng Lin; Weibo Song (Journal of Ocean University of China, 2004)

Pseudovorticella paracratera n. sp., a new marine peritrich ciliate (Ciliophora: Peritrichida) from north China - Daode Ji; Weibo Song; Alan Warren (Hydrobiologia, 2004)